2009
DOI: 10.1002/app.30061
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and thermal behavior of long branching polypropylene prepared by reactive extrusion

Abstract: Long-chain branching polypropylene (LCB-PP) was achieved by reactive extrusion in the presence of bifunctional monomer [1,6-hexanediol diarylate (HDDA)] and peroxide of dicumyl peroxide (DCP). Influences of HDDA and DCP concentrations on the branching efficiency were comparatively evaluated. Fourier transformed infrared spectroscopy (FTIR) results indicated that the grafting reaction took place, and HDDA has been grafted on PP skeleton. In comparison with initial PP, some modified samples showed lower melt flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 24 publications
(61 reference statements)
3
35
0
1
Order By: Relevance
“…Furthermore, as the concentration of LCBs increases, the shear‐thinning region becomes more appreciable, beginning at gradually lower frequencies. This behavior is typical of topological structures that get gradually more complex . An additionally interesting behavior can be also observed when the dynamic data are presented in this way.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, as the concentration of LCBs increases, the shear‐thinning region becomes more appreciable, beginning at gradually lower frequencies. This behavior is typical of topological structures that get gradually more complex . An additionally interesting behavior can be also observed when the dynamic data are presented in this way.…”
Section: Resultssupporting
confidence: 88%
“…The melting process of all polymers is very similar, with T m and Δ H m of the modified materials slightly lower than those of PPg. This is in agreement with most of the works in the literature that deal with long‐chain branched PPs . The results suggest that the presence of branches in the molecules somewhat reduces the size and amount of the crystal domains.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…For the pristine PP, the Cole‐Cole plot exhibits a shape of similar semicircle owing to its linear molecule structure. However, all the Cole‐Cole plots of PPs modified by the acrylate monomers deviate from semicircle and show an uptrend at high viscosity, indicating that a different relaxation mechanism and a long relaxation time . Besides, the curve of PP NPGDA is lower than that of pristine PP, which indicates that degradation reaction plays a main role in this free radical reaction due to the poor stabilization effect of NPGDA on the PP tertiary carbon radical .…”
Section: Resultsmentioning
confidence: 96%
“…These experiment results are consistent with those acquired from the torque curves. It is reported that Cole‐Cole plot ( η ′′‐ η ′), Figure C could be used to illustrate the long relaxation process . As shown in Figure C, the distinctions between pristine PP and modified PPs are obvious.…”
Section: Resultsmentioning
confidence: 96%